2017
DOI: 10.1038/s41598-017-16595-9
|View full text |Cite
|
Sign up to set email alerts
|

Exteroceptive expectations modulate interoceptive processing: repetition-suppression effects for visual and heartbeat evoked potentials

Abstract: Interoception refers to the signaling of internal bodily commands. Here, we explore repetition suppression of intero- and exteroceptive neural markers to test whether the perception and predictability of exteroceptive stimulus material affects their expression. Participants completed a repetition suppression paradigm in which angry or neutral facial expressions repeated or alternated. Participants received either an implicit (experiment 1) or explicit (experiment 2) cue enabling the formation of expectations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 75 publications
(92 reference statements)
11
47
1
Order By: Relevance
“…These results contrast with previous ERP studies reporting repetition suppression effects on early VEPs (e.g., Engell & McCarthy, 2014;Nemrodov et al, 2015;Vizioli et al, 2010). A recently published ERP study has shown that repetition of the same facial identity posing a negative expression leads to repetition suppression of both VEPs and HEP, in comparison to when posing a neutral expression (Marshall et al, 2017, see also Marshall et al, 2018). By contrast, in our paradigm the repetition manipulation was made in regards to the affective content of the facial expression, that is, emotion component, as opposed to the identity component.…”
Section: Affective Inference Does Not Impact Visual Cortical Responsescontrasting
confidence: 96%
See 4 more Smart Citations
“…These results contrast with previous ERP studies reporting repetition suppression effects on early VEPs (e.g., Engell & McCarthy, 2014;Nemrodov et al, 2015;Vizioli et al, 2010). A recently published ERP study has shown that repetition of the same facial identity posing a negative expression leads to repetition suppression of both VEPs and HEP, in comparison to when posing a neutral expression (Marshall et al, 2017, see also Marshall et al, 2018). By contrast, in our paradigm the repetition manipulation was made in regards to the affective content of the facial expression, that is, emotion component, as opposed to the identity component.…”
Section: Affective Inference Does Not Impact Visual Cortical Responsescontrasting
confidence: 96%
“…In the current study, affective repetition effects on cardiac interoceptive processing were only observed in repetition blocks, suggesting that the repetition effects were highly dependent on probability context. Our results are in line with previous evidence that highlight the role of expectations in repetition effects (Marshall et al, 2017;Marshall et al, 2018) supporting the idea that repetition suppression is a surprise-context-dependent phenomenon that occurs via probability context. The evidence that affective repetition effects were only present when the likelihood of repetitions was high suggests that the HEP modulation may result from global top-down modulation based on probability context (i.e., highrepetition probability) rather than from lower level sources of local prediction signals from the preceding trial.…”
Section: Context-dependent Affective Prediction Effects On Cardiac supporting
confidence: 92%
See 3 more Smart Citations